Consistency checking and combining measurement results for a wireless sensor network - Duta, M; Henry, M (Trans Tech Publications, 2008)
Two similar approaches are presented for performing consistency checking of measured data in cases where associated uncertainty values are provided. The key differences between the approaches concern the determination of a consistent subset, and the treatment of measured data deemed to fall outside that subset. The different approaches reflect the priorities of their respective domains of application, namely on-line sensor monitoring, and interlaboratory comparisons.